PROFIL PASAR DAGING - SAPI IMPOR DI KOTA YOGYAKARTA - , Dian Widiyanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Beef demand has been continuing to increase, resulting in the number of imported beef in Indonesia. The study was conducted to determine the structure of imported beef markets, market distribution, regulation, tariff policies and strategies of the traders in Yogyakarta City. A survey was conducted from November 2008 to November 2009 in Yogyakarta City to provide primary and secondary data. Respondent consists of distributors, hotels, restaurants, catering industry, supermarkets, wet markets, and meat shops. The market was found to be an oligopoly were two companies had market share of 55.3% (Indoguna company), 41.5% (Sukandadjaya company), and 3.2% (small companies selling processed meat). There was an increase of imported beef demand from of 69.473 tons (2008) to 94.22 tons (2009), distributed to hotels 31,27%, restaurants15,02%, catering industry 12,19% , supermarkets 34,27%, wet markets 1,15%, and meat shops 5,77%. In terms of meat class distribution and price, the retail was found to be Rp. 210,000/kg (class I , 52%) Rp.71,800/kg (class II, 12%), and Rp.20,400/kg (class III, 36%). The market share of imported beef in Yogyakarta city overall was 3.82% from total demand of beef. Government regulations was only dealt with the procurement process and the country of origin of meat permitted. Tariffs were imposed as much as 5% and 10% in the form income tax and added value tax, respectively. If the companies intend to expand the market share by entering wet markets, it is suggested 1) collaborates with meat seller in wet market to help in meat distribution, 2) educated the consumers to be familiar with frozen imported beef